2015
DOI: 10.5194/nhess-15-277-2015
|View full text |Cite
|
Sign up to set email alerts
|

The calamity of eruptions, or an eruption of benefits? Mt. Bromo human–volcano system a case study of an open-risk perception

Abstract: Abstract. In this paper we investigate the question not of how, but why people actively choose to live with continued exposure to considerable hazard. A field survey of the human-volcano interaction at Bromo Volcano was based on semi-structured interviews and focus group discussions. The recorded interviews were transcribed and analysed according to recurrent themes in the answers. Findings from field investigation were then confronted with previous existing concepts of human exposure to natural hazards. The r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 47 publications
2
44
0
3
Order By: Relevance
“…People consider that the volcano is a part of their daily culture and life. They have a unique culture that portrays volcano as the center of the God and the symbol of greatness [33].…”
Section: Community Behavior and The Challenges Of Volcano Eruptionmentioning
confidence: 99%
See 2 more Smart Citations
“…People consider that the volcano is a part of their daily culture and life. They have a unique culture that portrays volcano as the center of the God and the symbol of greatness [33].…”
Section: Community Behavior and The Challenges Of Volcano Eruptionmentioning
confidence: 99%
“…Differences in social, cultural and economic factors play an important role in the ability of communities to understand disasters and how they cope with disaster risks [51]. Like the Tenggerese people of the Bromo Mountains, they have five cultural adaptations that enable them to survive in the mountainous areas of resilience and high ability to return to their original state, attachment to place and knowledge of danger, the source of social and moral order, and catalyst for the process of change [33].…”
Section: Community Behavior and The Challenges Of Volcano Eruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…They could survive and anticipate the disasters by observing the occurring of natural phenomena prior to the disasters, such as the birds leaving the eruption center [27]. The snake bite cases give disadvantages for the people living near or in the slopes of the volcano, although in contrary it is useful to predict the volcano eruption, so that people can prevent it or evacute earlier.…”
Section: Ta Tamansarimentioning
confidence: 99%
“…Later, using in situ Multi-Gas analysis and remote spectroscopic measurements, Aiuppa et al [8] measured the composition and fluxes of volcanic gases released by Bromo. The social aspect of Bromo and its inhabitants has also been studied, where Bachri et al [9] investigated the reasons why people chose to live near Bromo despite the exposure to volcanic hazards and found that the interaction between humans and the volcanic environment at Bromo was multifaceted and complex.…”
Section: Introductionmentioning
confidence: 99%